Affective polarization in crosscutting communication networks: Offline and online evidence from Spain - Nordbrandt, Maria (Frontiers in Political Science, 2022)
Despite its potentially pernicious consequences for social relations and democracy, the study of affective polarization has only recently proliferated. Thus, the reasons driving this development—or its consequences—are not yet adequately understood. This article addresses the role of one specific factor frequently discussed in both academic and popular debate—namely, the role of crosscutting communication among people of different political leanings. It is a longstanding notion that crosscutting communication is crucial to overcoming the prejudice, polarization, and attitudinal biases brought on by streamlined information diets. However, there is empirical evidence to suggest that crosscutting experiences sometimes elevate polarization—especially when individuals also have access to like-minded views and when disagreement is perceived as intense. The study sheds light on the connection by testing hypotheses about the association between crosscutting communication and affective polarization in both offline and online modalities of political communication. The empirical analyses were based on panel data from the E-DEM project covering a random sample of Spanish citizens interviewed up to three times between November 2018 and May 2019—that is, the time running up to the Spanish national election in 2019. The results suggest that individuals who reported engagement in face-to-face discussions with supporters of various parties (crosscutting discussions) during this time reported significantly lower levels of affective polarization compared to engagement in discussions with co-partisans exclusively. Online crosscutting and consensual discussion experiences, however, were linked to comparable levels of anti-out-group sentiment, suggesting that concerns about the impact of online communication being different from offline communication in general—and perhaps more harmful—may be overstated. Descriptive evidence furthermore indicates that most respondents who engaged in political discussions had experiences of discussions with both co-partisans and supporters of opposing parties rather than co-partisans exclusively. Again, this was true for offline and online communication alike. Insofar as the results translate to other contexts as well, they indicate that future efforts to explain any surges in affective polarization should primarily be focused on other areas of inquiry.